THE APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL ASSISTED BY BLENDED LEARNING TO ENHANCE METACOGNITIVE AWARENESS - Varisky Dumanaw; Tiara Lestari Paembonan; Awal Mulia Rejeki Tumanggor (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Metacognitive awareness is essential in fostering students' ability to regulate their own learning processes, especially in complex subjects like analytical chemistry. This study investigates the effectiveness of a Problem Based Learning (PBL) model assisted by Blended Learning in enhancing metacognitive awareness among university students in the topic of UV-Vis spectroscopy. Using a quasi-experimental design, two groups were compared: an experimental group receiving PBL combined with Blended Learning, and a control group receiving conventional PBL. Data collection involved pretest and posttest cognitive assessments, metacognitive awareness questionnaires, and observation of student engagement on the Edmodo platform. The results demonstrate significant improvement in the experimental group’s posttest cognitive scores (mean = 85.59) compared to the control group (mean = 77.37), with effects also observed in metacognitive awareness and self-regulation skills (p < 0.05). These findings suggest that integrating Blended Learning into the PBL framework can effectively enhance cognition, metacognitive skills, and student motivation in chemistry education. The study encourages the adoption of this blended instructional strategy and further research on its wider applicability.